HUBUNGAN TINGKAT PENGETAHUAN REMAJA TENTANG SEKS PRANIKAH DENGAN PRILAKU SEKS PRANIKAH DI SMKN 1 BATUSANGKAR TAHUN 2016 - Putra, Yuhendri; MS, Fitriani (LPPM Universitas Prima Nusantara Bukittinggi, 2018)
According to the World Health Organization (WHO) 20% of 515,000 maternal deaths worldwide are caused by anemia. Anemia is a condition of decreased hemoglobin, hematocrit and erythrocyte counts below normal values. This study aims to determine the effect of green beans juice on hemoglobin levels of pregnant women with mild anemia trimester III. This was Quasi-Experiment with one-group pre-test design post-test design. The sample of the study were 16 pregnant women with mild anemia using purposive sampling technique. Each respondent is given treatment by giving green bean juice for as 250 cc, 2 twice per day for 7 days. Data were analyzed with Paired T-Test Sample. There was the influence of green beans on the increase of pregnant women's hemoglobin level but it is not very significant, this green bean juice should be used as a preventive effort in the prevention of anemia. Suggestions for promoting green beans juice in an attempt to prevent anemia in pregnant women.